2009
DOI: 10.1007/s11605-008-0711-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Surgical Complications and Preoperative Serum Hepatocyte Growth Factor in Hepatocellular Carcinoma Patients After Initial Hepatectomy

Abstract: Postoperative surgical complications could have a prognostic impact on overall survival in HCC patients after initial hepatectomy. Serum HGF could be a factor connected to complications and survival in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 25 publications
5
26
3
Order By: Relevance
“…HGF in serum is an indicator of ovarian carcinoma in females with a pelvic mass, and with poor prognosis in advanced ovarian cancer. Similar results have been demonstrated in studies evaluating HGF in gastric carcinoma, colorectal cancer and hepatocellular carcinoma (17)(18)(19). However, there has been no study evaluating HGF in NPC.…”
Section: Discussionsupporting
confidence: 83%
“…HGF in serum is an indicator of ovarian carcinoma in females with a pelvic mass, and with poor prognosis in advanced ovarian cancer. Similar results have been demonstrated in studies evaluating HGF in gastric carcinoma, colorectal cancer and hepatocellular carcinoma (17)(18)(19). However, there has been no study evaluating HGF in NPC.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies showed that high serum levels of HGF in patients with HCC negatively associated with OS and outcome [104][105][106] . In the recent SHARP study biomarkers analysis, patients treated with sorafenib experienced a decrease in a mean plasma level of HGF although; patients treated with placebo have mean HGF concentration increase [63] .…”
Section: Hepatocyte Growth Factormentioning
confidence: 98%
“…Mizuguchi et al [106] systemic therapies for patients with advanced HCC, no association between baseline AFP levels and prognosis was observed [66] . More interestingly, some authors evaluated the kinetics of AFP during treatment in HCC as a predictive marker of response or outcome.…”
Section: Poorer Prognosismentioning
confidence: 99%
“…[22][23][24][25], but these studies-conducted on tumor tissue (22)(23)(24) and hepatic vein (25) markers-have involved small numbers of patients. Biomarker evaluations in larger HCC patient populations, especially as part of randomized, placebo-controlled trials, may provide additional insight into the predictive and/or prognostic utility of specific markers.…”
Section: Introductionmentioning
confidence: 99%